2017
DOI: 10.1111/cas.13115
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous impact of alcohol consumption according to treatment method on survival in head and neck cancer: A prospective study

Abstract: Alcohol consumption is an established risk factor, and also a potential prognostic factor, for squamous cell carcinoma of the head and neck (HNSCC). However, little is known about whether the prognostic impact of alcohol consumption differs by treatment method. We evaluated the association between alcohol drinking and survival by treatment method to the primary site in 427 patients with HNSCC treated between 2005 and 2013 at Aichi Cancer Center Central Hospital (Nagoya, Japan). The impact of alcohol on prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 41 publications
2
36
0
2
Order By: Relevance
“…Negative effects of continued alcohol consumption go beyond the development of second primary cancers and recurrences, however. Evidence suggests that HNC survivors who continue to use alcohol are at an increased risk of needing gastrostomy tube feeding in the future, experiencing osteoradionecrosis of the jaw, poor prognosis as well as social effects such as unemployment and work disability . Indeed, other research has shown that the absence of alcohol use by HNC survivors was significantly associated with better quality of life …”
Section: Introductionmentioning
confidence: 99%
“…Negative effects of continued alcohol consumption go beyond the development of second primary cancers and recurrences, however. Evidence suggests that HNC survivors who continue to use alcohol are at an increased risk of needing gastrostomy tube feeding in the future, experiencing osteoradionecrosis of the jaw, poor prognosis as well as social effects such as unemployment and work disability . Indeed, other research has shown that the absence of alcohol use by HNC survivors was significantly associated with better quality of life …”
Section: Introductionmentioning
confidence: 99%
“…Major efforts to improve the survival of patients with head and neck cancer begin with identifying and reducing disparities of modifiable risk factors. Classically, the incidence and outcome of head and neck cancers have been associated with smoking and alcohol use, stage at presentation, age at diagnosis, and the presence of the human papillomavirus for oropharyngeal cancers . Now, studies are increasingly establishing the role of psychosocial factors in cancer survival.…”
Section: Introductionmentioning
confidence: 99%
“…Classically, the incidence and outcome of head and neck cancers have been associated with smoking and alcohol use, stage at presentation, age at diagnosis, and the presence of the human papillomavirus for oropharyngeal cancers. [1][2][3][4][5][6][7][8][9][10][11] Now, studies are increasingly establishing the role of psychosocial factors in cancer survival. That patients who are nonwhite or of lower socioeconomic status (SES) often fare worse than their counterparts is becoming more clear and has caught the interest of the field.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of an association between pre-treatment alcohol use and HNC mortality risk is conflicting. Some studies report an inverse association between alcohol intake and survival, 13,[19][20][21] whilst others have found little or no evidence of an effect. 17,22 Consequently, it is unclear whether any association of alcohol consumption with HNC cancer mortality is genuine, or the result of residual confounding by smoking (or other factors).…”
mentioning
confidence: 99%
“…17,22 Consequently, it is unclear whether any association of alcohol consumption with HNC cancer mortality is genuine, or the result of residual confounding by smoking (or other factors). Recently, it was suggested that the effects of alcohol intake on HNC survival may differ by treatment method and primary site, 21 but this study only included 427 individuals from a single cancer centre in Japan, emphasising the need for further research in this area.…”
mentioning
confidence: 99%